Melt Emulsions: Influence of the Cooling Procedure on Crystallization and Recrystallization of Emulsion Droplets and their Influence on Dispersion Viscosity upon Storage. Issue 3 (31st January 2022) - Reiner, Jasmin; Ly, Tran T.; Liu, Lingyue; Karbstein, Heike P.
Abstract: Emulsions with crystalline dispersed phase are widely used formulations in life sciences. Unfortunately, these products often are unstable resulting in changes of their rheological behavior. These changes could be linked to shape transformations of crystallized droplets, depending on the cooling rate in their production and temperature of storage. In a thermo‐optical method, shape changes were investigated in a broad range of constant cooling rates or cooling rate ramps close to industrial processes. Cooling at slow to moderate cooling rates (0.1–50 K min −1 ), as found in typical stirred vessel tanks, induced self‐shaping of droplets during crystallization, which resulted in platelet‐like particles and fibers, deviating greatly from the formerly spherical shape. In contrast, fast cooling as found in heat exchangers resulted in mostly spherical shapes less prone to recrystallization‐induced instabilities. Abstract : Crystalline dispersions are often unstable resulting in changes of their rheological behavior. These changes can be linked to shape transformations of crystallized droplets and their recrystallization behavior during storage. The influence of cooling procedure on particle shape and crystallization of droplets is investigated and related with its influence on particle recrystallization and alterations of dispersion characteristics during storage.